The relationship between blood urea nitrogen to serum albumin ratio and cardiovascular diseases, cardiovascular mortality, and all-cause mortality in patients with diabetes mellitus - Zhu, Hongwei; Xie, Wei; Wang, Peng; Jiang, ShuYuan; Hua, YunQi; Shao, Guo; Li, ZhiHui (Frontiers in Endocrinology, 2025)
BackgroundThe relationship between the Blood Urea Nitrogen to Albumin Ratio (BAR) and cardiovascular diseases in diabetes, as well as cardiovascular and all-cause mortality, is not yet entirely understood. This study aimed to examine the correlation between the serum urea nitrogen to albumin ratio and cardiovascular diseases, cardiovascular mortality, and all-cause mortality in diabetes.MethodsA total of 7043 adult diabetes patients were included from the NHANES database from 2001 to 2018. The relationship between BAR and cardiovascular diseases, cardiovascular mortality and all-cause mortality in patients with diabetes mellitus was verified using baseline characteristic analysis, multivariate logistic regression analysis, multivariate Cox proportional hazards model, Kaplan-Meier (K-M) analysis, smoothed fitted curves, and subgroup analysis.ResultsResults of the logistic regression analysis indicated a substantial positive association, between the BAR and the risk of cardiovascular disease in individuals with diabetes (HR, 1.09 [95% CI 1.06–1.12], p < 0.001). Cox regression analysis revealed a substantial positive association between the BAR and the risk of cardiovascular (OR, 1.13 [95% CI, 1.10–1.17], p < 0.001) and all-cause mortality (OR, 1.12 [95% CI 1.11–1.14], p < 0.001) in diabetes. The restricted cubic spline (RCS) curves indicated a non-linear relationship between BAR and the risk of cardiovascular disease, cardiovascular mortality, and all-cause mortality in diabetes (p < 0.01). The receiver operating characteristic (ROC) curves demonstrated that the BAR had superior predictive performance for cardiovascular risk (AUC: 0.648), cardiovascular mortality (AUC: 0.618), and all-cause mortality (AUC: 0.674) compared to the body mass index (BMI) (cardiovascular risk AUC: 0.525, cardiovascular mortality AUC: 0.563, all-cause mortality AUC: 0.571) and the weight-adjusted-waist index (WWI) (cardiovascular risk AUC: 0.579, cardiovascular mortality AUC: 0.497, all-cause mortality AUC: 0.570). These results underscore the enhanced ability of the BAR to discriminate between positive and negative outcomes, making it a more effective predictor than WWI. Kaplan-Meier analysis further verified the predictive capacity of BAR, for cardiovascular mortality and all-cause mortality in diabetes patients. Subgroup analysis revealed consistent associations between BAR and a variety of subgroups.ConclusionThe incidence of cardiovascular disease, cardiovascular mortality, and all-cause mortality was substantially elevated, in patients with diabetes with a higher BAR level. Cardiovascular disease, cardiovascular mortality, and all-cause mortality may be more prevalent among diabetic patients with elevated BAR levels. BAR is a novel marker for the prediction of cardiovascular disease, cardiovascular mortality, and all-cause mortality in diabetes.